ANALISIS KUALITATIF IMPLEMENTASI KEBIJAKAN WORK FROM HOME (WFH) PADA DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN MAJALENGKA - Tera Triyantara HRN (Jurnal Ilmu Administrasi CENDEKIA, 2021)
ABSTRACT This research is entitled An Qualitative Analysis The Implementation Of Work From Home (WFH) Policy At The Civil Registry Office Of Majalengka Regency. The background of this research is to find out how the implementation of WFH at the The Civil Registry Office Of Majalengka Regency, it is because The Civil Registry Office is an office that provides services to public. With the existence of WFH, certainly, more or less will hinder the process of administrative services to the public. The method used in this research is qualitative-descriptive method using two sources of data, which is primary data and secondary data. The research was carried out using the theory of public policy implementation according to Merilee S. Grindle, with research focus that the success of a public policy implementation can be measured from the achievement process, that whether or not the goal to be achieved and the extent to which the benefits are felt by the existence of the policy. From the results of the research it can be concluded that, the implementation of Work From Home policy At The Civil Registry Office Of Majalengka Regency it's quite effective and does’nt hinder the service process to the public, it’s because during implementation of WFH, an service to the public continuesly running and replaced with a WhatsApp-based online service system, namely si Lancar.  Keywords: Implementation, Work From Home Policy, The Civil Registry Office Of Majalengka Regency